Bending, Twisting, and Propulsion of Photoreactive Crystals by Controlled Gas Release - Yu, Chunjiao (2024)
The rapid release of gas by a chemical reaction to generate momentum is one of the most fundamental ways to elicit motion that could be used to sustain and control the motility of objects. We report that hollow crystals of a three‐dimensional supramolecular metal complex that releases gas by photolysis can propel themselves or other objects and advance in space when suspended in mother solution. In needle‐like regular crystals, the reaction occurs mainly on the surface and results in the formation of cracks that evolve due to internal pressure; the expansion on the cracked surface of the crystal results in bending, twisting, or coiling of the crystal. In hollow crystals, gas accumulates inside their cavities and emanates preferentially from the recess at the crystal terminus, propelling the crystals to undergo directional photomechanical motion through the mother solution. The motility of the object which can be controlled externally to perform work delineates the concept of “crystal microbots”, realized by photoreactive organic crystals capable of prolonged directional motion for actuation or delivery. Within the prospects, we envisage the development of a plethora of light‐weight, efficient, autonomously operating robots based on organic crystals with high work capacity where motion over large distances can be attained due to the large volume of latent gas generated from a small volume of the crystalline solid.